Multi-criteria analysis for OS-EMR software selection problem: A comparative study - Zaidan, A.A.; Zaidan, B.B.; Hussain, M.; Haiqi, A.; Mat Kiah, Miss Laiha; Abdulnabi, M. (Elsevier, 2015)
Abstract Various software packages offer a large number of customizable features to meet the specific needs of organizations. Improper selection of a software package may result in incorrect strategic decisions and subsequent economic loss of organizations. This paper presents a comparative study that aims to evaluate and select open-source electronic medical record (OS-EMR) software based on multiple-criteria decision-making (MCDM) techniques. A hands-on study is performed, and a set of OS-EMR software are implemented locally in separate virtual machines to closely examine the systems. Several measures as evaluation bases are specified, and systems are selected based on a set of metric outcomes by using AHP integrated with different MCDM techniques, namely, WPM, WSM, SAW, HAW, and TOPSIS. Paired sample t-test is then utilized to measure the correlations among different techniques on ranking scores and orders. Findings are as follows. (1) Significant differences exist among MCDM techniques on the basis of different integrations on ranking scores, whereas no significant differences exist among them when representing the ranking scores to the ranking orders in place of the technique scale. (2) The software GNUmed, OpenEMR, OpenMRS, and ZEPRS do not differ in ranking scores/orders of experiments for all MCDM techniques presented. On the contrary, discrepancies among the ranking scores/orders are more noticeable in other software. (3) GNUmed, OpenEMR, and OpenMRS software are the most promising candidates for providing a good basis on ranking scores/orders, whereas ZEPRS is not recommended because it records the worst ranking score/order in comparison with other OS-EMR software.